Growth Model of the Russian Economy on the Basis of Productivity of Aggregate Labor: a Cognitive Approach - V. I. Orekhov; T. R. Orekhova (Управление)
The article discusses the performance category of cumulative work on the basis of modern models of economic growth of Russia. The key problem of economic policy in conditions of crisis is determined. The advantages of introducing system of management of artificial intelligence and the balanced scorecard are given. The proposed by authors graphical interpretation of the three stages models of economic growth, with emphasis on the cognitive component of the study of economic growth is presented. The author’s brief description of the elements of modern growth model of the Russian economy through increased productivity is given.